Nutritional aspects and dietary benefits of “Silkworms”: Current scenario and future outlook - Mahanta, Deepak Kumar; Komal, J.; Samal, Ipsita; Bhoi, Tanmaya Kumar; Dubey, Vinod Kumar; Pradhan, Kiranamaya; Nekkanti, Aarthi; Gouda, M. N. Rudra; Saini, Varun; Negi, Nikita; Bhateja, Sheenam; Jat, Hansa Kumari; et al. (Frontiers in Nutrition, 2023)
Food is the moral right of all who are born into this world. The global demand for food is predicted to rise in the future as nations get wealthier and populations rise. It is estimated that by 2050, there will be an additional 2.5 billion people and a 70% increase in food demand. Crop yields are not increasing fast enough to support global needs and world agriculture facing several serious challenges. Therefore, insects can be a nutritious alternative to meet the ever-increasing food demand in the present and future scenario. The majority of insect consumption occurs in developing countries, with approximately 1,900 insect species consumed worldwide. Food and feed derived from them is of high quality, high feed conversion ratio and emits low level of greenhouse gases. Among Insects silkworm is beneficial to humans, not only because of their high nutritional value, but also because of their several pharmacological properties. Silkworm eggs, larvae and pupae contains high amount of proteins, oils, minerals, vitamins and several other beneficial components which are nutritious as well as have positive effect on human health. Studies have shown that silkworm pupae protect the liver, enhance immunity, inhibit apoptosis, inhibit cancer, inhibit tumor growth, inhibit microbial growth, regulate blood glucose and blood lipids and lower blood pressure. This review paper summerised the nutritional value of different life stages of silkworm, nutritional comparison of silkworm with the major human foods, effect of silkworm consumption on human health. This paper aim is to generate interest towards sericulture and improve human health by using silkworm as a nutritious food.